PENGEMBANGAN VIDEO ANIMASI PADA PEMBELAJARAN MATEMATIKA MATERI PECAHAN DI KELAS V SDN 14 BELANTI BARAT - Sintya Purnama Sari; Gusnita Efrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' low understanding of fractional content is due to learning that still dominates the use of lecture methods and textbooks so that abstract concepts are difficult to understand. The purpose of this research is to develop an animation video media based on the CapCut application in learning fractional content mathematics in Grade V of the SDN 14 Belanti Baraat and to test the level of validity, practicality and effectiveness of the developed media. The research uses the research and development (R&D) methodology with the ADDIE model which includes the analysis, design, development, implementation, and evaluation phases. Data collection techniques are carried out through observation, interviews, documentation, expert validation questionnaires, teacher and student feedback questionnaires, and learning outcomes testing (pre-test and post-test). The results of the study showed that animated video media achieved a validity value of 90.7% with a very valid category. The level of practicality based on the teacher's response reached 97.85% and the student's response was 88.62%, both of which are in the category of very practical. The effectiveness of the media was shown to increase in average student learning outcomes from 40.86 in the pre-test to 87.24 after reaching 100% of classical completion in the test. Thus, the CapCut-based animation video media has been declared valid, practical, and effective for use in fractional mathematics learning and is able to improve the concept understanding, learning interests, and learning outcomes of elementary school students.